2008
DOI: 10.1002/yea.1576
|View full text |Cite
|
Sign up to set email alerts
|

Novel stress responses facilitate Saccharomyces cerevisiae growth in the presence of the monocarboxylate preservatives

Abstract: Certain yeasts are relatively resistant to the small number of monocarboxylic acids allowed in food preservation, with the result that these preservatives often have to be used in high concentrations in order to prevent spoilage. When grown at slightly acid pH, Saccharomyces cerevisiae acquires elevated resistance to these acids by means of discrete stress responses. Acquisition of resistance to acetic acid involves loss of Fps1p, the aquaglyceroporin of the plasma membrane that facilitates the passive diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
64
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 67 publications
1
64
0
Order By: Relevance
“…A number of theories have been presented to explain the antifungal properties of weak acids, including acidification of the cytoplasm, anion accumulation, membrane perturbation, and ATP depletion (4,29,50). To what extent these various mechanisms contribute to the antifungal activities of weak acids is still unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…A number of theories have been presented to explain the antifungal properties of weak acids, including acidification of the cytoplasm, anion accumulation, membrane perturbation, and ATP depletion (4,29,50). To what extent these various mechanisms contribute to the antifungal activities of weak acids is still unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…7,33 In general, baker's yeast cells are known to be relatively resistant to monocarboxylic WOAs. 14,16 At least three different mechanisms are supposed to be responsible for that:…”
Section: Discussionmentioning
confidence: 99%
“…16,37,38 Yeast can extrude acid anions through the anion efflux pump Pdr12p, which has been found to mediate resistance to both AA and PA. 18 However, later works by the same research group reported that acetate did not induce expression of PDR12 gene, while PA did. 17,39 It was believed that expression of Pdr12p is controlled by the sole War1p transcriptional factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations